Teachers Strategy in Solving Students Ability to Read and Write Qur’an at Government Schools - Fitri Fitri; Kamaruddin Kamaruddin; Idhan Idhan (INTERNATIONAL JOURNAL OF CONTEMPORARY ISLAMIC EDUCATION, 2021)
This study discusses teachers strategy of Islamic Education in overcoming students difficulties of reading Al-Qur'an a State Junior High School. The problems that will be addressed included what strategies were used by the teachers in overcoming students difficulties in reading Al-Qur'an and who the strategies were implemented to solve the problems. In conducting the study, we used a qualitative case study method. The case of this study was a state junior high school in West Sulawesi province. Data were gathered through direct field observation, in-depth interviews which involve teachers and the school principle. We also analyzed written material, such as the school teaching activities, to understand how the teachres solve students difficulties in reading al-Quran. Our study found that the strategies to overcome students difficulties in reading al-Quran included the determination of the qualification of learners. Hold a special coaching for students who experience difficulties in reading Quran. Then the teachers made cooperation with fellow teachers and learners. Finally, the teachers familiarized the students to read Al-Qur'an.